Direct evaluation of peripheral airways using ultra-high-resolution CT in chronic obstructive pulmonary disease. Issue 120 (November 2019) - Tanabe, Naoya; Shima, Hiroshi; Sato, Susumu; Oguma, Tsuyoshi; Kubo, Takeshi; Kozawa, Satoshi; Koizumi, Koji; Sato, Atsuyasu; Togashi, Kaori; Hirai, Toyohiro
Highlights: A small airway <2 mm in diameter is a major pathological site in COPD. Small airways <2 mm in diameter cannot be evaluated with conventional CT. Ultra-high-resolution CT provides 1024 × 1024 matrix and 0.25 mm thickness image. Ultra-high-resolution CT clearly visualizes small airways 1–2 mm in diameter. The 6 th generation airways commonly <2 mm in diameter in COPD affect lung function. Abstract: Purpose: Disease in small airways <2 mm in diameter is a major pathology of chronic obstructive pulmonary disease (COPD). However, compared to airways <1 mm in diameter, the pathophysiological role of airways 1–2 mm in diameter remains unclear. This study analysed phantom and human COPD data to test the hypothesis that ultra-high-resolution computed tomography (U-HRCT) can accurately measure peripheral airways that are difficult to measure with conventional CT. Method: The lower limit of lumen sizes measurable on U-HRCT was determined using phantom tubes. In the cross-sectional data of 110 males with COPD who underwent U-HRCT (1024 × 1024 matrix, 0.25 mm slice thickness) and spirometry, all 3 rd (segmental) to 6 th generation airways of the right apical and basal posterior bronchus (RB1 and RB10) were analysed. Results: The errors in measuring the lumen area (LA) of phantom tubes ≥1.3 and 1.0 mm in diameter were within ±10 and -24%, respectively. The internal diameters for 70 and 62% of the 6 th generation RB1 and RB10 airways were <2 mm. The numbers of 6 th generation RB1 and RB10 airways decreased as the airflow limitation severity increased. Among the mean LA and sum of LA(sum-LA) of the 3 rd to 6 th generation airways, the sum-LA of the 6 th generation had the largest impact on airflow limitation. Conclusions: U-HRCT enables accurate and direct evaluation of peripheral airways 1–2 mm in diameter. The 6 th generation airways are commonly <2 mm in diameter, and the sum-LA can be a useful CT biomarker that reflects airflow limitation in COPD.